The effect of inventory turnover leverage and sales growth on profit growth at PT Matahari Department Store Tbk - Alivatus Cintia; Fida Oktafiani (Enrichment : Journal of Management, 2023)
The purpose of this research was to determine the effect of inventory turnover, leverage, sales growth on profit growth partially or simultaneously. In this research, it was used descriptive statistical data type with a quantitative approach. The data source used in this study were secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) in the form of company financial report data for the 2016-2021 period. This research was conducted at retail companies listed on the IDX with a sample of 1 company obtained through a purposive sampling technique and the method of data analysis used multiple linear regression with SPSS version 29. This research was conducted to provide insight into how these variables affect company profitability and contribute to overall financial performance. The results showed that inventory turnover, leverage, and sales growth had no effect on profit growth. The strength of the variable relationship in predicting the occurrence of profit growth is relatively large, namely 68.4%.